2018
DOI: 10.7150/jbji.29065
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Perforation by a Toothpick as Reason for Necrotizing Fasciitis

Abstract: Necrotizing fasciitis is an uncommon but often fatal disease. Given the various causes of necrotizing fasciitis, we report a case of sigmoid colon perforation caused by a toothpick subsequently resulting in fulminant necrotizing fasciitis of the retroperitoneum and right thigh successfully treated by hemipelvectomy and Hartmann´s procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“… Terminal ileum perforation Right pelvic region along iliopsoas muscle into buttock Bacteroides fragilis, Escherichia coli, and Prevotella spp. No No recollection 2018 Markus Rupp et al [ 4 ] 51 M Gas gangrene in the right lower abdomen and right leg. Surgical debridement was performed.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… Terminal ileum perforation Right pelvic region along iliopsoas muscle into buttock Bacteroides fragilis, Escherichia coli, and Prevotella spp. No No recollection 2018 Markus Rupp et al [ 4 ] 51 M Gas gangrene in the right lower abdomen and right leg. Surgical debridement was performed.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The mortality rate of psoas abscesses can reach 100% if left undiagnosed and untreated [ 1 ]. Moreover, psoas abscesses become more complicated to treat after they have progressed to necrotizing fasciitis [ 4 ]. The data of secondary psoas muscle abscess cause by ingested toothpick are limited in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our literature review, we were unable to identify a case of an immunocompetent host who developed necrotizing fasciitis without a penetrating injury or inciting infection. Unique cases have been reported that include necrotizing fasciitis in an atraumatic immunocompromised host, another case from an intestinal perforation of a toothpick, and a another case from a simple cat bite [ 5 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, these infections are likely more aggressive in patients with serious medical comorbidities such as diabetes, obesity, kidney disease, vascular disease, drug/alcohol abuse, or advancing age sepsis [3,4]. Mortality rate is variable but approaches 100% without any treatment which is why prompt diagnosis is vital Dr. Zachary P Herzwurm Dr. Cameron S Murphy Dr. B Gage Griswold Dr. Colton R J Webber Dr. Kyle M Mahoney [5]. These infections can be grouped into polymicrobial and monomicrobial with polymicrobial representing 75% sepsis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation